Mengubah Mindset Guru dalam Peningkatan Kompetensi untuk Menerapkan Kurikulum Merdeka Menggunakan Teknologi di SDN Sungai Miai 5 - Naila Azizah; Rahmadati .; Nor Hidayah; Aslamiah .; Diani Ayu Pratiwi (CV. ITTC INDONESIA, 2025)
The implementation of the Merdeka Curriculum at SDN Sungai Miai 5 faces two primary challenges: teachers’ continued reliance on traditional teaching methods and the limited integration of technology in classroom practices. These issues stem not only from a lack of exposure to digital tools but also from insufficient skills in applying them to support learning activities. This condition poses a significant obstacle to designing innovative, student-centered approaches in line with the core principles of the Merdeka Curriculum, such as project-based learning and differentiated instruction. This study aims to explore effective strategies to improve teacher competencies through mindset transformation and the enhanced use of technology, ultimately supporting the successful implementation of the Merdeka Curriculum at the primary school level. Using a qualitative approach with a case study method, data were collected through in-depth interviews and non-participatory observations involving several teachers. The data were analyzed using descriptive techniques, including data reduction, data display, and conclusion drawing, to obtain a comprehensive understanding of the challenges and solutions identified. The results indicate that targeted strategies such as technical mentoring, need-based professional development, the establishment of collaborative learning communities, and strong school leadership support are essential in facilitating teacher transformation. Furthermore, access to adequate digital infrastructure significantly boosts the adoption of technology-enhanced learning. Teachers have gradually demonstrated improvements in digital competence and have begun to implement more varied, contextual, and student-oriented learning strategies that reflect the spirit of the Merdeka Curriculum.